WECEP [Work Experience and Career Exploration Program] Guide A Curriculum Guide. - Illinois State Board of Vocational Education and Rehabilitation, Springfield. Div. of Vocational and Technical Education; Illinois State Board of Vocational Education and Rehabilitation, Springfield. Div. of Vocational and Technical Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
WECEP, a cooperative education program for 14- and 15-year-old potential dropouts in either elementary or high school grades, provides work experience in jobs approved by Federal and State laws. The guide is intended for use as a resource for teacher-coordinators of local WECEP programs and supplements another Illinois Division of Vocational and Technical Education publication, An Articulated Guide for Cooperative Occupational Education. The first section presents brief outlines of: the rationale of the programs, planning local programs, roles of teacher-coordinators, community relations, and the need for career education. The second and largest section contains units of study (understanding yourself, how to get a job, career planning, and career fields arranged by clusters). Each lesson includes teaching concepts, activities, and resource materials, and some lessons provide additional information or exercises. An extensive bibliography of current reference materials in all media, arranged by subject areas and source, and a shorter list of evaluation materials comprise the third section. The final section, an appendix, reproduces tax and social security forms, employment applications, sample letters, and legislation affecting WECEP. (MDW)
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Career Education; Cooperative Education; Curriculum Guides; Experimental Curriculum; Individual Development; Job Application; Potential Dropouts; Resource Materials; Secondary Education; Self Actualization; Work Experience; Work Experience Programs; Work Experience Career Exploration Program; Guides, General